(untitled) (Annals of Medical Research, 2023)
Aim: Numerous studies have demonstrated a clear relationship between high triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-C) and decreased insulin sensitivity, nonalcoholic fatty liver disease, and metabolic syndrome. Dysglycemia may result from increased insulin sensitivity. No study has examined the relationship between this ratio and dysglycemia in the literature. In this study, we aimed to determine if the TG/HDL-C ratio of 2.27 would serve as a marker for detecting dysglycemia in the oral glucose tolerance test (OGTT). Materials and Methods: This study consists of a retrospective and cross-sectional analysis of 101 patients aged 8.93-17.79 years who were assessed for overweight and obesity in pediatric endocrine outpatient clinics and underwent oral glucose tolerance test as a screening tool for prediabetes and/or type 2 diabetes. The patients’ anthropometric, physical examination, radiological and laboratory data were collected from the electronic and paper-based patient records. Results: In overweight and obese children, the TG/HDL-C ratios of 2.27 and higher were correlated with HOMA-IR and insulin levels, similar to previous studies (p <0.05). While basal fasting glucose was significantly higher in patients with dysglycemia (p< 0.05), there was no correlation between basal fasting insulin, HbA1C, TG/HDL-C ratio, BMI-SDS and dysglycemia. Conclusion: Although it was shown in this study that there is a relationship between an increased TG/HDL-C ratio and insulin level, no relationship was found with dysglycemia.